Airway remodeling: The Drosophila model permits a purely epithelial perspective - Ehrhardt, Birte; El-Merhie, Natalia; Kovacevic, Draginja; Schramm, Juliana; Bossen, Judith; Roeder, Thomas; Krauss-Etschmann, Susanne (Frontiers in Allergy, 2022)
Airway remodeling is an umbrella term for structural changes in the conducting airways that occur in chronic inflammatory lung diseases such as asthma or chronic obstructive pulmonary disease (COPD). The pathobiology of remodeling involves multiple mesenchymal and lymphoid cell types and finally leads to a variety of hardly reversible changes such as hyperplasia of goblet cells, thickening of the reticular basement membrane, deposition of collagen, peribronchial fibrosis, angiogenesis and hyperplasia of bronchial smooth muscle cells. In order to develop solutions for prevention or innovative therapies, these complex processes must be understood in detail which requires their deconstruction into individual building blocks. In the present manuscript we therefore focus on the role of the airway epithelium and introduce Drosophila melanogaster as a model. The simple architecture of the flies’ airways as well as the lack of adaptive immunity allows to focus exclusively on the importance of the epithelium for the remodeling processes. We will review and discuss genetic and environmentally induced changes in epithelial structures and molecular responses and propose an integrated framework of research for the future.